2013
DOI: 10.1017/s1041610213000847
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of anxiety in long-term care: examination of the Geriatric Anxiety Inventory (GAI) and its short form

Abstract: Both the GAI and GAI-SF appear to be useful tools for assessing anxiety among nursing home residents with psychological disorders. The GAI-SF may be a viable replacement for the GAI as a screener for anxiety in long-term care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 51 publications
2
25
0
Order By: Relevance
“…Specifically, the GAI demonstrated excellent internal consistency. This is consistent with previous research on the GAI (Gerolimatos et al, 2013) which found that the GAI was a reliable and valid measurement of anxiety in nursing homes. The GAI had significantly better internal consistency when compared to the GAS-LTC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Specifically, the GAI demonstrated excellent internal consistency. This is consistent with previous research on the GAI (Gerolimatos et al, 2013) which found that the GAI was a reliable and valid measurement of anxiety in nursing homes. The GAI had significantly better internal consistency when compared to the GAS-LTC.…”
Section: Discussionsupporting
confidence: 92%
“…The items are rated "agree" or "disagree" with higher scores indicating higher levels of anxiety. The properties of the GAI have been examined with community-dwelling older adults (Pachana et al, 2007;Byrne et al, 2010), older adults seeking outpatient clinical services (Pachana et al, 2007), and older adults in long-term care settings (Gerolimatos et al, 2013). A cut-off score of 10 shows specificity of 84% and sensitivity of 75% for detecting Generalized Anxiety Disorder (GAD), and a cut-off score of 8 was used for the detection of any anxiety disorder with a specificity of 80% and sensitivity of 78%.…”
Section: Methodsmentioning
confidence: 99%
“…Despite anxiety being one of the most common psychiatric conditions in later life (Gonçalves et al, 2011), only recently has interest gained momentum into anxiety among residents of aged care facilities (known variously as nursing homes, hostels, assisted living facilities, or long-term care/residential homes). This is surprising, particularly given that psychiatric disorders commonly precipitate admission into residential care (Luppa et al, 2010), and older residents represent an increasingly frail and medically ill group who are at increased risk for anxiety (Tolin et al, 2005;Gerolimatos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several researches have studied the psychometric properties of the GAI, including MárquezGonzález, Losada, FernándezFernández, & Pachana (2012), Gerolimatos, Gregg, & Edelstein (2013), Massena, Bom de Araújo, Pachana, & Camozzato de Pádua (2014), Yan, Xin, Wang, & Tang (2014), Gould, Segal, Yochim, Pachana, Byrne & Beaudreau (2014), Ball, Lipsius, & Escobar (2015), and Guan (2016). In general, they found that the GAI presents good psychometric properties such as internal consistency indexes (Cronbach's α) ranging from 0.91 to 0.93 among healthy communitydwelling older adults and in the psychogeriatric sample, respec tively.…”
Section: Introductionmentioning
confidence: 99%